Pulmonary vein isolation using Cryo Balloon ablation versus RF ablation using ablation index following the CLOSE protocol: a Prospective Randomized Trial. (24th May 2021) - Theis, C; Huber, C; Kaiser, B; Kaesemann, P; Pirozzolo, G; Bekeredjian, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The single procedure success rates of durable pulmonary vein isolation (PVI) for paroxysmal atrial fibrillation (AF) varies between 80 and 90 %. This prospective, randomized study investigated the efficacy of Cryo-Balloon PVI versus pulmonary vein isolation with RF-energy following the CLOSE protocol (ablation index (AI), interlesion distance ≤ 6 mm, surround flow catheter) in terms of single-procedure arrhythmia-free outcome, safety and procedural time. Methods and results A total number of 150 patients undergoing de-novo catheter ablation for paroxysmal AF were randomized to two different treatment arms in a 1:1 fashion. In group-A patients, PVI was performed with the 23 or 28 mm Cryo-Balloon (Articfront Balloon, Medtronic Inc). The ablation procedure in group B was performed with RF-energy, using AI and following the CLOSE protocol. During a mean follow-up of 15 ± 6 months after a single procedure, 69 (92%) patients of group A were free of arrhythmia recurrence versus 68 (90.67%) patients in group B (p = ns). A total of 10 patients (group A: 4, group B: 6; p = ns) underwent a redo-procedure. No difference between both groups was observed in terms of patients with PV recovery (group A: 2 (2, 67%) vs. group B: 3 (4%); p = ns). In 2 patients of group A and 3 patients of group B the PVs were durably isolated. Two patients of each group had continued paroxysmal AF but did not undergo redo-procedure. Significantly more patients of group A experienced AF recurrence during blanking period, whereas the outcome after 6 month showed no significant differences (group A 11 (14, 66%), group B: 6 (8%); p< 0.05). With regard to the procedural data, the procedure time was significantly shorter in group A (115.35 ± 15.38 versus 70.53 ± 16.13; p < 0.01), the flouroscopy time and dose area product showed no significant differences (Table 1). Both procedures were performed with a low number of complications, in group A two patients had a significant groin hematoma, no PE.  Conclusions: Cryo-Balloon PVI and PVI using ablation index following the CLOSE protocol are equally efficient in achieving durable PV-isolation. Approximately 7 % of the patients with clinically paroxysmal AF are having extra-pulmonary vein AF sources. Cryo-Balloon ablation leads to significantly more AF recurrence during the blanking period.